تقويم أهداف منهج العربية للناطقين بغيرها في الجامعة الأردنية من وجهة نظر المعلمين والمتعلمين - ربابعة، أحمد شحادة محمد (Ma'had al-Tarbiyyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2012)
The research aimed to evaluate the curriculum of Arabic language for non-Arabic speakers at the University of Jordan in 2011-2012, and to pinpoint its strong, and shortcoming points. The study tried to answer several questions revolving around the nature of the curriculum objectives; and whether it achieved the general targets of the Arabic language curriculum for non-Arabic speakers, the suitability of the learners targets, the extents of achieving the curriculum objectives & its content, a comparison between averages evaluation of the curriculum from the perspectives of study samples, and a comparison between the averages evaluation of the second sample (learners) based on their sex. The researcher used the descriptive approach, with suitable tools of; two questionnaires to collect the necessary data about the curriculum from the study samples, the descriptive statistics to investigate the extents gone to achieve between elements of the curriculum & its objectives from the perspectives of the research samples. The findings -theoretically- show that the objectives of evaluated curriculum don't violate the objectives of the Arabic language curriculums to non-Arabic speakers in general. According to the statistical results, the curriculum achieved its objectives moderately from the perspectives of the research samples in all of its elements. Based on the previous findings, the researcher recommended the need to review the objectives of the current curriculum, and that the planning of curriculum must precede the process of designing the curriculum, the need to consider the learner's objectives when planning and designing the curriculum, to pay attention to the methods of teaching according to the purposes of learners, to support the curriculum by a teacher's guide, and to increase attention to the training of language teachers for non-Arabic speakers.